Creation and manipulation of anyons in the Kitaev model - Dusuel, Sebastien; Schmidt, Kai Phillip; Vidal, Julien (Physical Review Letters, 2008)
We analyze the effect of local spin operators in the Kitaev model on the honeycomb lattice. We show, in perturbation around the isolated-dimer limit, that they create Abelian anyons together with fermionic excitations which are likely to play a role in experiments. We derive the explicit form of the operators creating and moving Abelian anyons without creating fermions and show that it involves multispin operations. Finally, the important experimental constraints stemming from our results are discussed.